2006
DOI: 10.4067/s0718-19572006000200004
|View full text |Cite
|
Sign up to set email alerts
|

Metales pesados en organismos marinos de la zona costera de la Patagonia argentina continental

Abstract: Hg, Cd, Pb, Cu and Zn were analyzed in mollusks, crustaceans (soft tissue -µg/g dry weight), seabirds and marine mammals (kidney, liver and muscle -µg/g wet weight), from Patagonian coast of Argentina. Levels of Hg were undetected or very low. Higher than allowable Cd levels for human consumption were recorded in some mollusks (up to 6.75 µg/g), even though its origin would be mainly natural. Pb concentrations in crustaceans from San Antonio bay (10.00 -13.20 µg/g) were related to an old mining activity. Conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 22 publications
4
29
0
14
Order By: Relevance
“…This point to an immediate threat, since in a previous study, Gil et al indicated concentration of pesticides under the detection limit of the method at Patagonia coasts, corresponding the higher value for pp´-DDE. In the same study, the concentration in mammals did not exceed 0.1 mg/L (Gil et al, 1997).…”
Section: Biotamentioning
confidence: 64%
“…This point to an immediate threat, since in a previous study, Gil et al indicated concentration of pesticides under the detection limit of the method at Patagonia coasts, corresponding the higher value for pp´-DDE. In the same study, the concentration in mammals did not exceed 0.1 mg/L (Gil et al, 1997).…”
Section: Biotamentioning
confidence: 64%
“…Two previous studies investigated metals in southern right whales calves found dead on the beach in PV. One study reported metals in liver, kidney and muscle of a single calf [24]. The second study reported liver and kidney levels in 45 dead calves [25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, North Atlantic right whales (Eubalaena glacialis) accumulate high levels of chromium [16]. Currently, the only data regarding metal concentrations in tissues of southern right whales come from dead calves [24,25]. Here we present results from a study in which we collected skin biopsies from live female southern right whales at Península Valdés and analyzed them for metals and selenium.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, A. ater has also been used for assessing the presence of cadmium in polluted marine environments on a more than 2000-kilometer-long coastline that extends from Walvis Bay in Namibia to Port Alfred on the coastline of South Africa [37]. In Chile and Argentina, A. ater is often used as a sentinel species to detect the bioaccumulation of pollutants, such as copper or cadmium, or toxic chemicals at different sites or following seasonal variations [14,[41][42][43][44]. It has also been used to study the disruptive effect of the natural estrogen E2 on male and female bivalves [45].…”
Section: A Ater As a Sentinel Organisms For Marine Ecosystemsmentioning
confidence: 99%